Developing Social Studies Teaching Materials for Conflict Resolution Education Using the Branch's ADDIE Research Method - Siti Fathimah; Bunyamin Maftuh; Elly Malihah; Erlina Wiyanarti; T. Heru Nurgiansah; Febriyanti Utami; Tesya Cahyani Kusuma (Emerging Science Journal, 2025)
This study aims to develop social studies teaching materials focused on conflict resolution education, addressing the unique needs of Class VII students in Pasaman, Indonesia. Conflict resolution is a crucial skill in today's global context, particularly in social studies, which integrates essential principles and competencies. Using Branch’s ADDIE research method, the study highlights the urgent need for a specialized guidebook tailored to Pasaman's local context and cultural nuances. Data collection revealed that 57.6% of students had low comprehension of conflict resolution, 28.2% medium, and 14.1% high. These findings emphasize the importance of differentiated instructional materials that cater to diverse learning needs. The proposed guidebook is designed not only to improve conflict resolution skills but also to incorporate elements of local wisdom, fostering a more relevant and engaging learning experience. The study further underscores the collaborative role of stakeholders in developing materials that align with students' understanding levels and cultural backgrounds. By bridging the gap between theory and practice, this research offers a model for creating inclusive, context-specific teaching strategies. The novelty of this study lies in its focus on local adaptation, contributing to a more effective learning process and supporting efforts to cultivate peace and resilience in educational settings.